2019
DOI: 10.1111/ijfs.14324
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical and technological properties of beef burger as influenced by the addition of pea fibre

Abstract: Summary This study aimed to evaluate the physicochemical characteristics and sensory attributes of beef burgers with the addition of pea fibre as a partial substitute of meat or fat. Three formulations were prepared: control (CON) – similar to the commercial formulation; fibre/less meat (FLM)—5% meat reduction and addition of 1% pea fibre; fibre/less fat (FLF)—7% fat reduction and addition of 1% pea fibre. Non‐significant differences were obtained for pH, colour parameters (L* and b*), texture profile, cooking… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 32 publications
(68 reference statements)
1
9
0
3
Order By: Relevance
“…However, pH values found in the present research were similar to those found in beef burgers by other authors [41,42]. Besides the significant differences observed among treatments, there is no clear trend and the values were similar.…”
Section: Proximate Composition and Physicochemical Parameters Of Beef Burgerssupporting
confidence: 88%
“…However, pH values found in the present research were similar to those found in beef burgers by other authors [41,42]. Besides the significant differences observed among treatments, there is no clear trend and the values were similar.…”
Section: Proximate Composition and Physicochemical Parameters Of Beef Burgerssupporting
confidence: 88%
“…A textura do hambúrguer cozido foi avaliada em cinco replicatas pelo teste de Análise de Perfil de Textura (TPA), onde as amostras receberam a compressão de um prato promovendo uma curva de deformação e gerando seis parâmetros de textura: fraturabilidade, dureza, coesividade, adesividade, elasticidade e mastigabilidade (Carvalho et al, 2017;Polizer-Rocha et al, 2019).…”
Section: Análise Instrumental De Texturaunclassified
“…Os hambúrgueres comerciais apresentam altos teores de sódio, podendo chegar a até 34% de suas recomendações diárias preconizadas pela FAO/OMS (Oliveira et al, 2014), sendo um produto cárneo que se destaca entre as categorias de alimentos pactuados Brazilian Journal of Development, Curitiba, v.7, n.2, p. 13396-13415 feb. 2021 para redução de sódio (Mitterer-Daltoé et al, 2017;Carvalho et al, 2019;Polizer-Rocha et al, 2019;Silva et al, 2020). Neste sentido, a ANVISA estabeleceu o nível máximo de 740mg de sódio em 100g de hambúrguer como meta (Brasil, 2013;Inguglia et al, 2017).…”
Section: Introductionunclassified
See 1 more Smart Citation
“…Previously, various natural compounds, such as lemon albedo [3], oat fiber [4], whey protein [4], pea fiber [5], aloe vera [6], and quince seed gum [7], have been used to improve the quality of meat products.…”
Section: Introductionmentioning
confidence: 99%